2013
DOI: 10.1002/sca.21072
|View full text |Cite
|
Sign up to set email alerts
|

Roughness parameter selection for novel manufacturing processes

Abstract: This work proposes a method of roughness parameter (RP) selection for novel manufacturing processes or processes where little knowledge exists about which RPs are important. The method selects a single parameter to represent a group of highly correlated parameters. Single point incremental forming (SPIF) is used as the case study for the manufacturing process. This methodology was successful in reducing the number of RPs investigated from 18 to 8 in the case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In contrast to the nanoscale, at the microscale, all the roughness parameters are correlated (Table ) nevertheless, profile values are slightly differently related by their correlation degree to surface values. These findings are comparable to previous studies (Nowicki, ; Rosén et al ., ; Ham and Powers, ) however, the different correlation values obtained by Ham et al is due to the different averaging methods. In their study the mean of three calculations was computed while in ours the median of 16 calculations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast to the nanoscale, at the microscale, all the roughness parameters are correlated (Table ) nevertheless, profile values are slightly differently related by their correlation degree to surface values. These findings are comparable to previous studies (Nowicki, ; Rosén et al ., ; Ham and Powers, ) however, the different correlation values obtained by Ham et al is due to the different averaging methods. In their study the mean of three calculations was computed while in ours the median of 16 calculations.…”
Section: Discussionmentioning
confidence: 91%
“…Surface features significantly condition many technological and biomedical applications of biomaterials (Ham and Powers, ). Surface roughness and surface wettability can significantly determine major aspects of biological interactions and, subsequently, allow to predict the eventual failure or success of an implant‐prosthetic treatment (Park et al ., ; Gittens et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters presented in Table I, are best suited and recommended for this geometry work, several authors in their research and procedures used tool diameters between 8 and 12 mm, high RPM and feed rates relative to the depth of cut [7] - [13], has been shown that the lower step, the surface quality and formability of the material are much better, considering cutting times are greater. Step depth (mm)…”
Section: Resultsmentioning
confidence: 99%
“…However, typically correlation analysis was used for surfaces after the same kind of machining. Terry and Brown et al [ 112 ] analyzed ground surfaces, Ham and Powers [ 113 ] surfaces after single-point experimental forming, Reizer et al [ 114 ] textured surfaces and Etxeberria et al [ 115 ] surfaces from biomaterials. Many works on this topic were related to two-process textures [ 45 , 106 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Measurement and Characterization Of Two-process Random Surfacesmentioning
confidence: 99%